PENGARUH DUKUNGAN ORANGTUA TERHADAP PRESTASI AKADEMIK SISWA FASE E DI SMAN 6 BATANG HARI - Devi Fitriana; Siti Amanah; Affan Yusra (STKIP Subang, 2026)
This study aims to determine the influence of parental support on the academic achievement of phase E students at SMA Negeri 6 Batang Hari. Using an ex post facto method quantitative approach, the study involved 75 samples from 279 students through purposive sampling. Data were obtained from parental support questionnaires and grade documentation, then analyzed using normality, linearity, simple regression, and determination coefficients with SPSS 22. The results showed that parental support had a significant effect on academic achievement (sig. 0.003 < 0.05), but the contribution was only 19.2%, while 80.8% was influenced by other factors such as self-motivation, learning environment, and the role of teachers. This research is expected to be an input for parents and schools in improving learning support as well as a reference for further research